Chilling injury alleviation of Queen pineapple cv. ‘Sawi’ fruit by acetyl salicylate immersion - Sangprayoon, Preyanuch; Supapvanich, Suriyan; Youryon, Pannipa; Wongs-Aree, Chalermchai; Boonyaritthongchai, Panida (My University, 2020)
Chilling injury (CI) is the main problem affecting quality of Queen pineapple (Ananas comosus L.) fruit during cold storage. The purpose of this paper was to investigate the application of acetyl salicylate (ASA) on CI alleviation of pineapple fruit cv. Sawi during storage at 13 ± 1 °C for 10 d. The pineapples were dipped in ASA solution at the concentrations of 2.5 or 5.0 mM for 1, 2 or 3 h and untreated fruits were used as control treatment. The biochemical-related parameters to CI incidence of tissue adjoining to the core were determined after the fruits were left at 25 °C for 2 d. The results show that 5.0 mM ASA immersion for 1 h alleviated internal browning incidence and lowered CI score compared to other treatments. The treatment also maintained high lightness (L*) value and low colour difference (ΔE*) value of tissue adjoining to the core. Compared to control treatment, the 5.0 mM ASA immersion lowered browning index, malondialdehyde concentration, polyphenol oxidase activity and TP concentration as well as increased antioxidant capacity and ascorbic acid concentrations of tissue adjoining to the core. Therefore, 5.0 mM ASA immersion for 1 h is an effective alternative alleviating CI of Queen pineapples during cold storage.
Keywords: Acetyl salicylic acid; Antioxidant activity; Chilling injury; Enzymatic activity; Internal browning; Queen pineapple cv. Sawi